2020
DOI: 10.1371/journal.pone.0228030
|View full text |Cite
|
Sign up to set email alerts
|

The wavelet power spectrum of perfusion weighted MRI correlates with tumor vascularity in biopsy-proven glioblastoma samples

Abstract: BackgroundWavelet transformed reconstructions of dynamic susceptibility contrast (DSC) MR perfusion (wavelet-MRP) are a new and elegant way of visualizing vascularization. Wavelet-MRP maps yield a clear depiction of hypervascular tumor regions, as recently shown. ResultsThere was a strong correlation between wavelet-MRP power spectrum (median = 4.41) and conventional relative cerebral blood volume (median = 5.97 ml/100g) in Spearman's rankorder correlation (κ = .83, p < .05). In a logistic regression model, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In the 10/17 patients who underwent needle biopsy, the stereotactic coordinates of the sampling sites were imported in the 3D Slicer Dataset as a 5 mm diameter spherical volume, similarly to what was previously described by other authors ( Jun et al, 2006 ; Barajas R. F. et al, 2012 ; Gates et al, 2019 ; Rotkopf et al, 2020 ), in order to take into account the maximum reported accuracy error in Euclidean distance reported in the literature ( Roth et al, 2018 ). Each histopathological specimen, labeled according to the order of resection, was then analyzed in comparison to the corresponding voxels and habitats in the 3D Slicer Dataset.…”
Section: Methodsmentioning
confidence: 99%
“…In the 10/17 patients who underwent needle biopsy, the stereotactic coordinates of the sampling sites were imported in the 3D Slicer Dataset as a 5 mm diameter spherical volume, similarly to what was previously described by other authors ( Jun et al, 2006 ; Barajas R. F. et al, 2012 ; Gates et al, 2019 ; Rotkopf et al, 2020 ), in order to take into account the maximum reported accuracy error in Euclidean distance reported in the literature ( Roth et al, 2018 ). Each histopathological specimen, labeled according to the order of resection, was then analyzed in comparison to the corresponding voxels and habitats in the 3D Slicer Dataset.…”
Section: Methodsmentioning
confidence: 99%
“…Ki67 is a marker of cell proliferation; higher values are associated with a higher proliferation index and consequently a higher tumor grade. A high proliferation index was related to vascularization and to a higher relative cerebral blood volume (rCBV) in glioblastoma ( 13 , 168 ), and an inverse correlation was seen between the Ki-67 proliferation index and the apparent diffusion coefficient (ADC) across glioma grades ( 13 ). Positive correlations between the Ki-67 proliferation index and metabolite alterations of choline over creatine ratio, lactate over creatine ratio, and myo-inositol were observed with MRS ( 169 ).…”
Section: Non-invasive Diagnosis Of Gliomasmentioning
confidence: 99%
“…1B. While the calculation of conventional parameters like CBF, CBV, time to peak (TTP), and mean transit time (MTT) is well-established and a mainstay of neurooncological and neurovascular diagnosis, novel processing methods like wavelet-based analysis [22,23], Bayesian vascular models [24], and control-point interpolation methods [25] may be able to capture pathological changes better. In addition, direct inference from the tissue residuum function may be able to capture important features which are missed by calculated single parameters.…”
Section: Perfusion Modelingmentioning
confidence: 99%